Establishing a physical health monitoring service for patients on depot antipsychotic medication. (7th March 2021) - Gill, M.; McKenna, K.; McCauley, M.; Gulzar, M.
Abstract : Introduction: Patients with major mental illness are recognised to be at risk of premature death for a multitude of reasons. This initiative aimed to improve the physical health monitoring of patients prescribed depot antipsychotic medication in a catchment area of ~36 000 in Ireland. Objectives: International best practice recommends monitoring of blood tests, physical parameters such as weight, BMI, waist circumference and blood pressure, and side effects of patients prescribed antipsychotic medication. A clinic was established to target these interventions. Methods: A cohort of patients receiving antipsychotics in long-acting injectable form was chosen. A twice-yearly, multidisciplinary health monitoring clinic was established. Evaluation involved an audit of medical records which measured the proportion of those attending the clinic who had blood test monitoring and physical parameters recorded. Results: Before the clinic's implementation, 30% of patients had evidence of some blood test monitoring, 9% had evidence of complete blood testing and one patient had evidence of physical health parameters having been recorded. One year after the implementation 78% of patients had evidence of some blood test monitoring, 61% had evidence of full blood test monitoring and 100% had evidence of physical parameters recorded. Conclusions: The clinic was positively received by patients, and led to improved teamwork. Recommendations include organising concurrent psychiatric and phlebotomy clinics so that patients may avail of psychiatric review and blood testing at a single appointment. As a result of the increased focus on physical health monitoring, a similar project is planned to target all patients prescribed antipsychotics.